Inhibition of HBV Expression in HBV Transgenic Mice Using AAV-Delivered CRISPR-SaCas9 - Li, Hao; Sheng, Chunyu; Liu, Hongbo; Wang, Shan; Zhao, Jiangyun; Yang, Lang; Jia, Leili; Li, Peng; Wang, Ligui; Xie, Jing; Xu, Dongping; Sun, Yansong; et al. (Frontiers in Immunology, 2018)
The chronic production of hepatitis B viral (HBV) antigens could cause inflammation and necrosis, leading to elevation of liver enzymes from necrotic hepatocytes, hepatitis, cirrhosis, hepatocellular carcinoma, and liver failure. However, no current treatment is capable of significantly reducing HBsAg expression in patients. Our previous studies had confirmed the ability of CRISPR-Cas9 in disrupting HBV cccDNA. Here, to inhibit HBV expression efficiently in the mouse model of chronic HBV infection, the miniaturized CRISPR-SaCas9 system compatible with a HBV core region derived guide-RNA had been packaged in recombinant adeno-associated virus (AAV) type 8, which lowered the levels of serum HBsAg, HBeAg, and HBV DNA efficiently in HBV transgenic mice during 58 days continuous observation after vein injection. It further confirms the potential of the CRISPR-Cas9 technique for use in hepatitis B gene therapy.